Visita del Presidente de la República. (UNED, 1994)
Aparecen Josett Altmann Borbón, junto a su esposo, José María Figueres Olsen (Presidente de la República), Celedonio Ramírez Ramírez (rector), Luis Fernando Díaz (Vicerrector de planificación) y José Joaquín Villegas (Vicerrector Acádemico)